Northwestern Argentina: a center of genetic diversity of Lemon Verbena (Aloysia citriodora Paláu, Verbenaceae) - Di Leo Lira, Paola Maria del Rosario (2013)
The aerial parts of lemon verbena (Aloysia citriodora Paláu) are worldwide used due to their medicinal and aromatic properties. The essential‐oil and acteoside contents have been proposed as the main quality markers for their pharmacological and organoleptic features. The northwestern region of Argentina has been repeatedly proposed as the place of origin for this species. For this reason, the essential‐oil yields and chemical compositions of leaves of 25 populations of lemon verbena from both wild collections and experimental crops from this region were studied. Plants from six different collections were subsequently grown on the same experimental parcel located at Cerrillos, Salta province, during more than seven years. In addition, the acteoside contents determined in all the samples collected in 2010 showed significant variations (from 0.5 to 4.0%). Large differences were observed in the essential‐oil composition and yields, which ranged from 0.4 to 2.1% (v/w). Nevertheless, most of the samples complied with the European Pharmacopoeia specifications. A remarkable chemical diversity with at least four clearly defined chemotypes was detected in this region. Therefore, it would be urgent to encourage actions to protect these genotypes of lemon verbena in the northwestern Argentina.